Vegetative propagation method influence on the antioxidant complex of Vaccinium corymbosum L. cultivars - Rupasova, Zhanna A.; Zadalya, Victoria S.; Chizhik, Olga V.; Filipenia, Veronika L.; Pavlovsky, Nikolay B. (Journal of the Belarusian State University. Ecology, 2021)
There are presented the results of a comparative study in an experimental culture in the central agro-climatic zone of Belarus, the influence of the method vegetative propagation of plants (cuttings and microclonal) on antioxidant and enzymatic (catalase, peroxidase and polyphenol oxidase)activity of fruits of early ripening (Weymouth) and late ripening (Elizabeth and Atlantik) varieties V. corymbosum L. It was shown that against the background of significant genotypic differences dependence of the studied characteristics of the antioxidant complex on the method reproduction, the fruits of meristemic plants were characterized by 5–21 % higher activity of catalase and especially peroxidase in comparison with traditional analogues, but at the same time 13 % lower activity of polyphenol oxidase in varieties Weymouth and Atlantik and 8 % higher in Elizabeth. Based on analysis correlations between the indicated components of the antioxidant a complex of plant fruits obtained in different ways, on the one hand, and the content in them of ascorbic and hydroxycinnamic acids, pectin substances, actually anthocyanins, leukoanthocyanins, catechins and flavonols, on the other hand, the differences between meristem and traditional plants have been established according to sources of antioxidant and enzymatic activity.
Keywords: blueberry; cultivars; cutting and microclonal methods of vegetative propagation; berries; antioxidant activity; enzymes; catalase; peroxidase; polyphenol oxidase